Evaluation of Tumour Necrosis Factor-Alpha and Interleukin-1beta in an Experimental Pyelonephritis Model Induced with Planktonic and Biofilms Cells of Pseudomonas aeruginosa - Rahul Mittal; Saroj Sharma; Sanjay Chhibber; Kusum Harjai (Canadian Journal of Infectious Diseases and Medical Microbiology)
Urinary tract infections may induce severe inflammation, transient impairment in renal function and scar formation, ranging in severity from acute symptomatic pyelonephritis to chronic pyelonephritis, and have the potential to lead to renal failure and death. In the present study, the relationship between production of tumour necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), neutrophil recruitment, bacterial colonization and tissue damage was investigated using a mouse model of acute ascending pyelonephritis induced with planktonic and biofilm cells of Pseudomonas aeruginosa. Neutrophil influx correlated with rise in TNF-α and IL-1β, indicating an association between these cytokines and neutrophil infiltration. However, biofilm cells of P aeruginosa induced higher levels of TNF-α and IL-1β leading to higher neutrophil infiltration causing tissue damage, assessed in terms of malondialdehyde, lactate dehydrogenase and glutathione content, which may have contributed to bacterial persistence compared with their planktonic counterparts. The results of the present investigation suggest that exaggerated cytokine production during P aeruginosa-induced pyelonephritis causes tissue damage operative through neutrophil recruitment leading to bacterial persistence in host tissues. The findings of the present study may be relevant for the better understanding of disease pathophysiology and for the future developments of preventive strategies against pyelonephritis based on anti-inflammatory intervention.